The Indirect Effect of Avoidant Motives for Sex on the Pathways From Childhood Maltreatment to Risky Sex Behaviors - Ellis, Robyn A. (Journal of interpersonal violence, 2023)
Literature supports a strong link between engagement in risky sex and childhood maltreatment, with engagement in risky sexual behavior proposed as a manifestation of avoidant coping. Sex motives refer to underlying motivations for engaging in sex such as increased intimacy, or peer pressure. Limited research has examined the role of sex motives on the relationship between childhood maltreatment and risky sex. This study sought to examine this path between childhood maltreatment types and later engagement in risky sex through sex motivations that seek to avoid or reduce negative affect (i.e., sex to cope and sex to affirm self-esteem). A sample of sexually active undergraduate women (n = 551) completed a series of questionnaires on childhood maltreatment, risky sexual behavior, and motivations for sexual intercourse as part of a larger parent study on revictimization. Path analysis was conducted to examine differential indirect effects of childhood maltreatment on risky sex (i.e., sex with a stranger and hookup behaviors). Results suggested sex to cope with negative affect mediated the relationship between emotional abuse, sexual abuse, physical neglect, and hookup behavior. Only an indirect path between childhood emotional abuse and sex with a stranger was identified through sex to cope. Emotional abuse was the only maltreatment to predict sex to affirm, but sex to affirm did not predict risky sex outcomes. Findings provide support for differential pathways from various forms of childhood maltreatment, specifically sexual abuse, emotional abuse, and physical neglect, to increased risky sex as a manifestation of avoidant coping. Furthermore, results support the call for more inclusion of nonsexual forms of childhood maltreatment in studies of risky sex and avoidant coping as a potential intervention target for risky sexual behavior regardless of childhood maltreatment type.